THE EFFECT OF THE NUMBER OF AUDIT COMMITTEE MEETINGS, ECO-EFFICIENCY AND COMPANY SIZE ON THE VALUE OF MINING COMPANIES LISTED ON THE IDX 2020 – 2022. - Sipayung, Chiara; Pangaribuan, Hisar; Siagian, Valentine (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study was to determine the effect of the number of audit committee meetings, eco-efficiency and company size on firm value in mining companies listed on the Indonesia Stock Exchange in 2020 - 2022. This study uses quantitative methods with a sample of 38 companies using purposive sampling totaling 114 data, the statistics used include descriptive statistics, normality test, glejser heteroscedasticity test, partial t-test, simultaneous f-test, and coefficient of determination test with the help of SPSS 27 software. The results of this test indicate that there is no significant effect of the number of audit committee meetings on firm value, eco-efficiency has a significant negative effect on firm value, company size has a significant positive effect on firm value in mining companies listed on the IDX. The results of this study are a new challenge for future researchers to develop in terms of the breadth of time and industry to be able to describe why eco-efficiency has a negative relationship with firm value.Keywords : Number of Audit Committee Meetings, Eco-Efficiency, Company Size, Company Value.